2022
DOI: 10.3389/fnut.2022.878979
|View full text |Cite
|
Sign up to set email alerts
|

Egg and Dietary Cholesterol Intake and Risk of All-Cause, Cardiovascular, and Cancer Mortality: A Systematic Review and Dose-Response Meta-Analysis of Prospective Cohort Studies

Abstract: ObjectiveThis systematic review and meta-analysis of prospective cohort studies examined the associations between egg and dietary cholesterol intake and the risk of mortality from all causes, including cardiovascular disease (CVD) and cancer.MethodsWe searched PubMed, Scopus, ISI Web of Knowledge, and Google Scholar until April 2021, as well as references to the relevant articles retrieved. Random-effects models were used to calculate summary relative risk (RR) and 95% confidence intervals (CIs) for the highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 90 publications
0
4
1
Order By: Relevance
“…Additionally, it should be noted that it is not our intention to recommend a high intake of eggs, which contain relatively high levels of cholesterol, for the prevention of IHD, as high levels of cholesterol in the blood are clearly a cause of dyslipidemia [33]. The conclusions of this study are opposed to the findings of many prospective cohort studies that have reported a positive association between egg consumption and the risk of cardiovascular disease or total mortality [8,9]. The reason for the different results from such cohort studies may be related to the fact that the data used in this study included an average egg intake of 21.5 ± 17.1 g/day, with a maximum of 106.14 g/day.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Additionally, it should be noted that it is not our intention to recommend a high intake of eggs, which contain relatively high levels of cholesterol, for the prevention of IHD, as high levels of cholesterol in the blood are clearly a cause of dyslipidemia [33]. The conclusions of this study are opposed to the findings of many prospective cohort studies that have reported a positive association between egg consumption and the risk of cardiovascular disease or total mortality [8,9]. The reason for the different results from such cohort studies may be related to the fact that the data used in this study included an average egg intake of 21.5 ± 17.1 g/day, with a maximum of 106.14 g/day.…”
Section: Discussioncontrasting
confidence: 60%
“…In a recent cohort study of 30,835 people in China, a negative correlation between egg consumption and risk of death was also reported [6]. In contrast, a prospective cohort study of approximately 520,000 Americans and an updated meta-analysis in 2022 found that high egg consumption was associated with an increased risk of CVD [7][8][9]. Other studies have shown similar results, with these findings thought to be due to the increased cholesterol intake from egg consumption [8,10].…”
Section: Introductionmentioning
confidence: 94%
“…A further SRMA also found that overall consumption of each additional egg/day was associated with a small but significant increase in risk of CVD of 4% [ 51 ]. However, the other three SRMA looking at risk of CVD found no significant effects of egg consumption [ 52 , 53 , 54 ] and studies on CVD mortality largely found no association between egg intake and risk of death from CVD [ 49 , 55 , 56 , 57 , 58 ]. The exception was the SRMA by Yang et al, which reported an overall 7% increased risk of CVD mortality with each increment of 1 egg/day [ 59 ].…”
Section: Results: Risk Assessmentmentioning
confidence: 99%
“…But, a recent meta-analysis which comprised 33 cohort studies with a mixture of worldwide populations found that egg intake was not associated with the risk of mortality from all causes (RR the highest versus lowest level = 1.02, 95%CI = 0.94–1.11) [ 64 ]. A meta-analysis concluding nine studies on dietary cholesterol intake and mortality demonstrated a significantly increased mortality risk with cholesterol intake in the US studies but no associations in the non-US studies [ 65 ]. These discrepant egg/cholesterol–mortality associations across populations may be due to differences in dietary patterns and lifespan disease status across sociodemographics and ethnicities [ 64 ].…”
Section: Discussionmentioning
confidence: 99%